AMPKα is critical for enhancing skeletal muscle fatty acid utilization during in vivo exercise in mice. Issue 5 (21st January 2015) - Fentz, Joachim; Kjøbsted, Rasmus; Birk, Jesper B.; Jordy, Andreas B.; Jeppesen, Jacob; Thorsen, Kasper; Schjerling, Peter; Kiens, Bente; Jessen, Niels; Viollet, Benoit; Wojtaszewski, Jørgen F. P.
ABSTRACT: The importance of AMPK in regulation of fatty acid (FA) oxidation in skeletal muscle with contraction/exercise is unresolved. Using a mouse model lacking both AMPKα1 and ‐α2 in skeletal muscle specifically (mdKO), we hypothesized that FA utilization would be impaired in skeletal muscle. AMPKα mdKO mice displayed normal respiratory exchange ratio (RER) when fed chow or a high‐fat diet, or with prolonged fasting. However, in vivo treadmill exercise at the same relative intensity induced a higher RER in AMPKα mdKO mice compared to wild‐type (WT = 0.81 ± 0.01 (sem ); mdKO = 0.87 ± 0.02 (sem ); P < 0.01), indicating a decreased utilization of FA. Further, ex vivo contraction‐induced FA oxidation was impaired in AMPKα mdKO muscle, suggesting that the increased RER during exercise originated from decreased skeletal muscle FA oxidation. A decreased muscle protein expression of CD36 (cluster of differentiation 36) and FABPpm (plasma membrane fatty acid binding protein) (by ~17‐40%), together with fully abolished TBC1D1 (tre‐2/USP6, BUB2, cdc16 domain family member 1) Ser 237 phosphorylation during contraction/exercise in AMPKα mdKO mice, may impair FA transport capacity and FA transport protein translocation to sarcolemma, respectively. AMPKα is thus required for normal FA metabolism during exercise and muscle contraction.—Fentz, J., Kjøbsted, R., Birk, J. B., Jordy, A. B., Jeppesen, J., Thorsen, K., Schjerling, P., Kiens, B., Jessen, N., Viollet, B., Wojtaszewski, J. F. P. AMPKα is critical for enhancing skeletal muscle fatty acid utilization during in vivo exercise in mice. FASEB J. 29, 1725‐1738 (2015). www.fasebj.org